Catalase and Superoxide Dismutase Enzymes Activities in Flaxseed (Linum Usitatissimum) Extract - Yucebilgic, Guzide; Bozdemir, Yurdanur (Asian Journal of Chemistry, 2010)
In this study, catalase (E.C.1.11.1.6) and superoxide dismutase (EC 1.15.1.1) activities were determined in the extract of flaxseed (Linum usitatissimum) with high antioxidant effect. Activities were determined after homogenization, ultracentrifugation and PD-10 (Sephadex G- 25M) column chromotography steps. After the ultracentrifugation step, catalase and superoxide dismutase specific activities were found as 15.94 U/mg prot. and 2.05 U/mg prot., respectively. After desalting with PD-10 column chromotography, catalase and superoxide dismutase specific activities were found as 17.56 U/mg prot. and 4.90 U/mg prot., respectively.